American Board of Dental Public Health diplomate survey, 2021: Competency domains and practice. (13th December 2022) - Macek, Mark D.; Zavras, Athanasios; Tomar, Scott L.; Cappelli, David; McKernan, Susan; Timothe, Peggy; Okunseri, Christopher
Abstract: Objective: To describe current Dental Public Health diplomates and list the competency domains that diplomates considered either essential or optional elements of their practice. Methods: The American Board of Dental Public Health administered an electronic survey to active and life member diplomates during September 2021. The survey included 101 items in three sections: (1) Education and Work Experience; (2) Dental Public Health Tasks; and (3) Demographics. The Dental Public Health Tasks section asked individuals how essential work‐related tasks were to their current practice. Descriptive analyses were conducted using SAS. Results: The overall response rate was 82.6% (157 eligible of 190 returned). Most respondents were women, 35 to 54 years of age, and either non‐Hispanic white or non‐Hispanic Asian. Twice as many had DDS or DMD degrees than BDS degrees. The vast majority completed a Dental Public Health residency and received masters level training from an accredited program. About three‐fourths worked in the United States and held a U.S. license. More than 37% reported a second doctoral degree and 70% worked in academia. Responses to questions about tasks closely aligned with working in academia and less so with positions related to advocacy, regulation, and program evaluation. Conclusions: Current diplomates are concentrated in academia. If this trend continues, it may be necessary to restructure the competencies, so training and skills acquisition remain timely and relevant. The specialty may also need to encourage future generations to consider non‐academic positions so Dental Public Health remains an impactful component of the public health care system.